Factors associated with the uptake of immediate postpartum intrauterine contraceptive devices (PPIUCD) in Rwanda: a mixed methods study - Chris Adrien Kanakuze; Dan Kabonge Kaye; Priscilla Musabirema; Pascal Nkubito; Scovia Nalugo Mbalinda (BMC Pregnancy and Childbirth, 2020)
Abstract Background Rwanda has a high unmet need for family planning which could be reduced by improving access to postpartum intrauterine contraceptives device (PPIUCD) insertion. The objective of the study was to assess the prevalence and factors associated with the uptake of PPIUCD among postpartum women in Muhima Hospital. Methods A concurrent mixed-method study was used. Three hundred eight three (383) immediate postpartum mothers, and 10 health services providers were interviewed using a structured questionnaire and in-depth interviews respectively. Logistics regression was done to assess for factors associated with PPIUCD uptake and thematic analysis was used for qualitative data. Results The prevalence for PPIUCD use was 28.1%, women who had spontaneous vaginal delivery were more likely to take up PPIUCD (Adjusted Odds Ratio (AOR) 2.623, 95% CI = 2.017–6.507 compared to those who had cesarean section; women who received PPIUCD counselling during the antenatal period were more likely to use PPIUCD ((AOR 2.072, 95% CI = 1.018–4.218) as compared to those who didn’t receive any form of counselling; mothers who received spouse approval were more likely to use PPIUCD (AOR 2.591,95% CI = 1.485–4.492); as compared to those who didn’t receive any spousal approval; women who had more than one child were more likely to use PPIUCD (AOR =2.265, 95% CI = 1.472–3.163) as compared to prime gravida; Mothers with birth to pregnancy interval less than two years were more likely to use PPIUCD (AOR =2.123, CI =1.477–2.706) as compared to those who had birth to pregnancy interval more than 2 years. From the qualitative findings, health education of mothers and partners on PPIUCD, training of health care providers, and availability of supplies to provide PPIUCD influenced the use of PPIUCD. Conclusion The acceptability to use for PPIUCD was high in this population. PPIUCD uptake was associated with normal birth, PPIUCD counselling, spousal approval, parity, birth interval, level of education. Health education of mothers and partners on PPIUCD, training of health providers, and availability of supplies to provide PPIUCD influenced uptake of PPIUCD.